Concept analysis in healthcare research - COUGHLAN, MICHAEL; RYAN, FRANCES; CRONIN, PATRICIA (My University, 2010)
Background: In recent years there has been an increasing interest in concept analysis as a means of establishing conceptual clarity about phenomena of interest within healthcare disciplines. This emergence is associated primarily with the recognition that a set of well developed key concepts pertaining to a discipline's domain of interest is an essential pre-requisite to building its scientific research base. Concept analysis focuses on concepts that are abstract and about which there is some ambiguity of meaning. Within healthcare disciplines these are mainly behavioural concepts that are concerned with understanding health and illness experiences. Content: There are a number of approaches to concept analysis that appear to have some similarities but which possess essential philosophical differences. This article examines the ontological and epistemological underpinnings of concepts and concept analysis. Methods of concept analysis that represent the various philosophical positions are presented and a critique of their limitations is offered. Conclusions: Concept analysis, using a structured framework, is means of identifying characteristics and attributes of abstract or ill-defined concepts with the purpose of achieving clarity. However, it can be a difficult and time consuming process that requires rigorous attention at all stages if the outcome is to be meaningful for knowledge and theory development and ultimately, practice.
PUBLISHED
Keywords: Concept Analysis; Healthcare